2020
DOI: 10.3906/tar-1909-2
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous cysteine alleviates mercury stress by promoting antioxidant defence in maize (Zea mays L.) seedlings

Abstract: Introduction Higher plants develop several adjustments to almost all different environments. Due to their immobile structure, plants are constantly subjected to abiotic and biotic stress factors that negatively affect plant growth, development, and reproduction (Rejeb et al., 2014). The impact of unfavourable conditions on the ecosystem is increasing at an alarming rate due to the rapid increase in soil and water pollution and destruction of vegetation through the excessive release of wastes produced by human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 62 publications
3
3
0
Order By: Relevance
“…Hg also upregulated GS1, GS2, MT2a, and MT3, implying that Hg stimulates the transcriptional regulation for synthesis of GSH and MTs. Recent study has shown that exogenous Cys increased the GSH content of maize seedlings in presence of Hg (Aysin et al, 2020). Our results also revealed that exogenous Cys further increased the expression of GSH synthesis related genes GS1 and GS2.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…Hg also upregulated GS1, GS2, MT2a, and MT3, implying that Hg stimulates the transcriptional regulation for synthesis of GSH and MTs. Recent study has shown that exogenous Cys increased the GSH content of maize seedlings in presence of Hg (Aysin et al, 2020). Our results also revealed that exogenous Cys further increased the expression of GSH synthesis related genes GS1 and GS2.…”
Section: Discussionsupporting
confidence: 80%
“…ROS scavenging is accompanied by an antioxidative defense system that comprises both enzymatic and nonenzymatic antioxidants, which maintain the redox state in plants. It has previously been shown that exogenous Cys increases the expression of SOD and CAT, but not GR, under Hg stress in maize seedlings (Aysin et al, 2020). Our results also revealed a variable modulation of the transcript levels of various enzymatic antioxidants by exogenous Cys depending on the exposure period.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations